Analisis Regresi Data Panel pada Angka Partisipasi Murni Jenjang Pendidikan SMP Sederajat di Provinsi Jawa Barat pada Tahun 2018-2021 - Karunia Rahayu Ayu; Muhammad Kasim Aidid; Zulkifli Rais (Program Studi Statistika Fakultas MIPA UNM, 2023)
Pure Enrollment Rate (APM) is the ratio of school-age children to the corresponding age population and is expressed as a percentage. Regression analysis is a statistical analysis method that aims to see the relationship between a dependent variable and one or more independent variables. Regression using panel data is called the panel data regression model. Panel data is a combination of time series and cross-section data. This study aims to determine the modeling of regression analysis with panel data regarding the Pure Participation Rate (APM) at the junior high school education level in West Java Province in 2018-2021 and to determine the factors that affect the level of Pure Participation Rate (APM) at the junior high school education level in West Java Province in 2018-2021. Based on the model selection carried out by conducting the Chow Test, Hausman Test, and Breucsh-Pagan Test, the best model is the Random Effect Model. From the random effect model, it is known that the factor or variable that has a very significant effect on the Pure Participation Rate (APM) of equivalent junior high schools in West Java province is the student-to-school ratio variable (X1).